High mutation burden in the checkpoint and micro-RNA processing genes in myelodysplastic syndrome. - Ivan Sergeevich Moiseev; Nikolay Yurevich Tcvetkov; Ildar Munerovich Barkhatov; Maria Vladimirovna Barabanshikova; Dmitrii Sergeevich Bug; Natalya Vitalievna Petuhova; Artem Valerievich Tishkov; Evgenyi Alexandrovich Bakin; Ekaterina Andreevna Izmailova; Alena Igorevna Shakirova; Alexandr Dmitrievich Kulagin; Elena Vladislavovna Morozova (PLoS ONE)
A number of sequencing studies identified the prognostic impact of somatic mutations in myelodysplastic syndrome (MDS). However the majority of them focused on methylation regulation, apoptosis and proliferation genes. Despite the number of experimental studies published on the role of micro-RNA processing and checkpoint genes in the development of MDS, the clinical data about mutational landscape in these genes is limited. We performed a pilot study which evaluated mutational burden in these genes and their association with common MDS mutations. High prevalence of mutations was observed in the genes studied: 54% had mutations in DICER1, 46% had mutations in LAG3, 20% in CTLA4, 23% in B7-H3, 17% in DROSHA, 14% in PD-1 and 3% in PD-1L. Cluster analysis that included these mutations along with mutations in ASXL1, DNMT3A, EZH2, IDH1, RUNX1, SF3B1, SRSF2, TET2 and TP53 effectively predicted overall survival in the study group (HR 4.2, 95%CI 1.3-13.6, p = 0.016). The study results create the rational for incorporating micro-RNA processing and checkpoint genes in the sequencing panels for MDS and evaluate their role in the multicenter studies.